PENENTUAN KELAYAKAN FINANSIAL USAHA PRODUKSI PUPUK ABC PADA CV.XYZ DUSUN SEBOTU KABUPATEN SANGGAU - SIAHAAN, DAPOT SAMUEL (Jurnal TIN Universitas Tanjungpura, 2017)
CV. XYZ start production of fertilizers Star in February 2010 until October of 2011 with total production and turnover of as much as 3360 units, or approximately 168 tons. After that the fertilizer production standstill owing Reviewed Reviewed fertilizer sales results taken away by one of the employees of CV. XYZ. The cessation of production of fertilizers stars resulted in a loss of Rp. 81,711,319, - on the CV. XYZ. After the vacuum during Â± 5 years, CV. XYZ planning to produce fertilizers star back in 2016. Based on these problems, then to reproduce the star fertilizer needed to improve the financial feasibility analysis clappers that would be obtained by CV. XYZ for more leverage and can cover the losses it had suffered, which is valued at RP. 81,711,319, -. The method used in analyzing the financial feasibility of the business of production of fertilizers stars consist of: NPV (Net presnt Value), IRR (Internal Rate of Return), PP (Payback Period), ROI (Return On Investment), BEP (Break Even Point) and analysis sensitivity such as sensitivity analysis of the decline in sales (10%), the sensitivity analysis the increase in fixed costs (10%) and sensitivity analysis of variable costs increase (20%). Results of the determination of the financial feasibility of fertilizer production enterprises using the star with the provisions of the loan capital by 20%, 30% and 40% financially feasible to be implemented again by CV. XYZ. Dilaksanakanya back with fertilizer business stars, CV. XYZ can restore back losses amounting to Rp. 81,711,319, - who had suffered on fertilizer production stars the period of 2010 through 2011. A sensitivity analysis that goes into the category is feasible only on sensitivity sales decline of 10% with a capital loan of 20% and 30%, a sensitivity increase variable cost of 20% with a capital loan of 20% and 30%, the combined sensitivity of the drop in sales and the increase in fixed costs by 10% with a capital loan of 20%, the combined sensitivity of the increase in fixed costs by 10% and the increase in variable costs by 20% with a capital loan of 20% and 30%. Keywords: Financial Feasibility Analysis, Net Present Value, Internal Rate Of Return, Payback Period, Return On Investmen, Break Even Poin